Biological factor of breaches of psychological health and its influence on healthy lifestyle of students of special medical group. - Vovk L.V (Kharkov National Pedagogical University, 2011)
The results of monitoring concerning an impact of biological factors on mental health of students who are related to special medical group are observed. 64 students have taken part in experiment, which were divided info 4 groups, three experimental and one checking. It has been proved that breaches of adaptation are expressed in deterioration of health, physical condition and motor activity of students. It is established that disadvantage biological factors limit ability to work, disturb the intellectual function, worsen social adaptation of the students.